Gene Expression of Antioxidant Metabolic Enzymes in Grape Extracts - Cai, Huitian; Zhang, Yi; Qiu, Zhehan; Luo, Peihuan (Cellular and Molecular Biology, 2022)
Fruit can use its structural characteristics to stabilize the excess electrons of free radicals and prevent cell aging, which is the main source of antioxidants supplementation. In the current study, the expression of antioxidant metabolic genes was evaluated in fruit extract. Seventy mice were divided into one control group and six experimental groups. Six experimental groups were fed 0.1g of grape extract daily for 3, 7, 10, 14, 21, 24 and 30 days, respectively. The antioxidant activity of fruit extract was tested by antioxidant metabolic enzyme gene expression in the liver and kidney of different experimental groups. The results showed that grape extract could effectively enhance SOD activity, LPL relative expression and FAS relative expression in mice liver tissue; grape extract could effectively increase SOD relative expression, TrxR2 relative expression and CAT relative expression in mice kidney tissue; grape extract could effectively reduce MDA activity in mice liver tissue, and increase and decrease the extent of MDA activity and the duration of feeding in mice. The proportion of fruit extracts showed that fruit extracts could effectively improve the antioxidant performance of the body.